A biopolítica e os dispositivos de majoração da vida - Camarote, Pedro Machado (2014)
Foucault´s concept of biopolitics, situated at the intersection of political practices and medical fields, sexuality, race wars, security and the economy, allows us to understand certain forms of action by the establishment upon life in contemporary societies. The section that was presented indulges the author´s criticism towards the economically oriented and repressive representations of the establishment, as well as the transformations that occurred in the transition from sovereignty to bio-power. Furthermore, it seeks to show the mechanisms of life extension that came about from social medicine and the sexual device, and runs through some of the revelations on the matter in Foucault´s work